Medical marijuana laws, traffic fatalities, and alcohol consumption - D. Mark Anderson; Daniel I. Rees (Institute for the Study of Labor (IZA), 2011)
To date, 16 states have passed medical marijuana laws, yet very little is known about their effects. Using state-level data, we examine the relationship between medical marijuana laws and a variety of outcomes. Legalization of medical marijuana is associated with increased use of marijuana among adults, but not among minors. In addition, legalization is associated with a nearly 9 percent decrease in traffic fatalities, most likely to due to its impact on alcohol consumption. Our estimates provide strong evidence that marijuana and alcohol are substitutes.
urn:nbn:de:101:1-201111303449
Keywords: I00; I1; 330; medical marijuana; traffic fatalities; alcohol consumption; Drogenkonsum; Medizin; Alkoholkonsum; Produktsubstitution; Straßenverkehrsunfall; USA